A DNS Reflection Method for Global Traffic Management - Huang, Cheng; Holt, Nick; Wang, Y. Angela; Greenberg, Albert; Li, Jin; Ross, Keith W. (USENIXATC'10 Proceedings of the 2010 USENIX conference on USENIX annual technical conference, Boston, MA, 2010)
An edge network deployment consists of many (tens to a few hundred) satellite data centers. To optimize enduser perceived performance, a Global Traffic Management (GTM) solution needs to continuously monitor the performance between the users and the data centers, in order to dynamically select the “best” data center for each user. Though widely adopted in practice, GTM solutions based on active measurement techniques suffer from limited probing reachability. In this paper, we propose a novel DNS reflection method, which uses the GTM DNS traffic itself to measure the performance between an arbitrary end-user and the data centers. From these measurements, the best data center can be selected for the user. We have implemented and deployed a prototype system involving 17 geographically distributed locations within the Microsoft global data center network infrastructure. Our evaluation of the prototype shows that the DNS reflection method is extremely accurate and suitable for GTM. In particular, at the 95 percentile, the measured latency is 6 ms away from Ping, and the selected data center is 2 ms away from the ground-truth best.